Evaluasi Usability Academic Managements System Poltekkes Kemenkes Palembang Menggunakan Metode SUS - Evi Yulianingsih; Aprilia Intan Wahyuni (HK-Publishing, 2022)
AbstractThe Academic Management System (AMS) is an information system created to assist the academic management of the Health Polytechnic of the Ministry of Health of Palembang. This system is used by several types of users, namely, students, lecturers, financial admins, PMB admins, and Academic admins. In this system there is a whole flow of students starting from registering to submitting a thesis and graduation. Students go through a series of steps in this system, from registering to writing a thesis to receiving their diploma. When it comes to measuring how user-friendly an application is, researchers used the System Usability Scale (SUS) with ten statements as a gauge. An overall sample size of 356 people was used in this study, which had lecturers and students as inclusion criteria. A proportional random sampling technique was used to select the respondents at random, with particular attention paid to the proportion of each population category represented in the sample. After testing 356 respondents, representing each faculty, the final result was a score of 66.5. So it can be said that the AMS Poltekkes Kemenkes Palembang is in the acceptable category. On the adjective rating scale, the AMS Poltekkes Kemenkes Palembang is included in the Good category. And on the AMS Poltekkes rating scale it is included in rank D. As a result, it can be concluded that the system is both user-friendly and capable of being used as an information system.Keywords: Academic Management System, Usability, System Usability Scale AbstrakAcademic Management System (AMS) merupakan sistem informasi yang dibuat untuk membantu pengelolaan akademik Poltekkes Kemenkes Palembang. Sistem ini digunakan oleh beberapa jenis pengguna yaitu, mahasiswa, dosen, admin keuangan, admin PMB, dan admin Akademik Siswa melalui serangkaian langkah dalam sistem ini, mulai dari mendaftar hingga menulis tesis hingga menerima diploma mereka. Ketika mengukur seberapa ramah pengguna suatu aplikasi, peneliti menggunakan System Usability Scale (SUS) dengan sepuluh pernyataan sebagai pengukur. Besar sampel keseluruhan 356 orang digunakan dalam penelitian ini, yang memiliki dosen dan mahasiswa sebagai kriteria inklusi. Teknik pengambilan sampel acak proporsional digunakan untuk memilih responden secara acak, dengan perhatian khusus diberikan pada proporsi setiap kategori populasi yang diwakili dalam sampel. Setelah dilakukan pengujian terhadap 356 responden, yang mewakili setiap fakultas, maka didapatlah hasil akhir yaitu skor 66,5. Sehingga dapat dikatakan AMS Poltekkes Kemenkes Palembang termasuk kategori acceptable. Pada skala adjective rating AMS Poltekkes Kemenkes Palembang termasuk dalam kategori Good. Dan pada skala peringkat AMS Poltekkes termasuk pada peringkat D. Hasilnya, dapat disimpulkan bahwa sistem ini ramah pengguna dan mampu digunakan sebagai sistem informasi.Kata kunci: Academic Management System, Usability, System Usability Scale